ANALYSIS OF TILAPIA CULTIVATION - Andrean Djanuandra; Trisna Insan Noor; Ivan Sayid Nurahman (Jurnal Ilmiah Mahasiswa Agroinfo Galuh, 2023)
Tilapia is one of the fishery commodities that are widely cultivated by the community today. Economically, tilapia cultivation is very profitable and also very supportive for the fulfillment of community nutrition. The purpose of this study was to determine the performance of cultivation, costs, revenues, income from tilapia rearing business and the feasibility of tilapia rearing business. This study used a qualitative method which was then analyzed descriptively. The informants in this study were members of the Bina Mekar fish farming group in Ciawang Village, Leuwisari District, Tasikmalaya Regency.The results of this study indicate that the average tilapia cultivation carried out by the Bina Bloom fish culture group is in accordance with the tilapia rearing cultivation procedure recommended by the government. The average total cost of tilapia enlargement is Rp. 6,132,646,51 and the average revenue for enlargement business is Rp. 7,680,000.00 and the average income of tilapia cultivation is Rp. 1,561,435.4 The tilapia rearing business carried out by the Bina Bloom fish farming group is feasible, with an R/C ratio of 1,218.